The Burden of Chronic Obstructive Pulmonary Disease COPD in Stable Patients and its Association with Inflammatory Biomarkers and Body Mass Index - Ibrahim , Samaa D.; Jasim , Ali L. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a progressive airflow limitation that is preventable but not curable. It is associated with persistent symptoms that cause a considerable burden on individual productivity at work, and daily activities, and reduced quality of life, also burdening the healthcare system and society.Objectives: The study aims to measure the burden of COPD on patients in terms of daily activities and work productivity. It also seeks to investigate some inflammatory biomarkers' levels and their correlation with selected outcomes.Methods: A cross-sectional study on 120 stable COPD patients who were diagnosed and treated according to the GOLD guidelines at Kirkuk General Hospital's chest and Internal Medicine consultation clinics, and in private internist clinics in Kirkuk City, Iraq between January and April 2023. The Work Productivity and Activity Impairment Questionnaire (WPAI-COPD) measured the Burden of COPD. The symptom burden was assessed by the COPD assessment test (CAT). The level of IL-6 monoclonal antibodies was measured via a Roche Cobas 6000 analyzer and TNF-α using the ELISA sandwich technique. All these devices and machines were authorized by the Ministry of Health, Iraq.Results: The mean age was (54.1 ± 8.12) years, 62.5% being males and 37.5% being females; 41.7% were public sector employees, and 39.2% were self-employed. Due to COPD, the overall work loss was (45.9±18.91) days, the mean percentage of absenteeism was (10.9% ± 12.31%), activity impairment was (47.5% ±17.79%) among all patients, presenteeism was (40.8 ± 15.05%), and COPD-related retirees were 14.2% of the study group. The mean CAT score (19.3±5.63) was high, and the most troubling symptom among patients was chest tightness.  WPAI-COPD scores were higher in older age and longer disease duration. The levels of biomarkers were above the reference ranges, the mean IL-6 level was (69.4 ± 35.29) pg/ml, and the mean TNF-α was (72.3 ± 22.45) pg/ ml.Conclusions: COPD patients exhibit a disease burden in terms of productivity loss at work and activity impairment that increases with ageing and disease duration. COPD patients with low BMI are more prone to a decline in lung functions and to worse symptoms